The Influence of Work-Life Balance and Workload on Job Stress: The Mediating Role of Psychological Well-Being among Employees of PT Pegadaian Terandam Branch - Dinda Saputri; Muhammad Oceano Fauzan (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of work-life balance and workload on job stress and investigates the mediating role of psychological well-being among employees of PT Pegadaian Terandam Branch. Research Method: A quantitative research design with a census approach was employed, involving all 60 employees of PT Pegadaian Terandam Branch as respondents. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.7. Results and Discussion: The findings indicate that work-life balance has a significant negative effect on job stress and a significant positive effect on psychological well-being. Conversely, workload has a significant positive effect on job stress and a significant negative effect on psychological well-being. Psychological well-being also has a significant negative effect on job stress. It serves as a complementary partial mediator in the relationships between work-life balance and job stress as well as between workload and job stress. Implications: The findings highlight the importance of promoting work-life balance, managing workload effectively, and enhancing employees' psychological well-being as strategic approaches to reducing job stress and improving organizational performance. Originality: This study extends the application of the Conservation of Resources Theory by demonstrating the mediating role of psychological well-being in explaining the relationships between work-life balance, workload, and job stress among employees of a state-owned financial service institution.